CLT in Chines Major’s Comprehensive Chinese Course – A case study of Khon Kaen University, Thailand - Sirisuwilai, Watcharapon (European Journal of Social Science Education and Research, 2021)
Nowadays Chinese language is become one of the most important foreign language in Thailand reflexing by the growing popularity of the Chinese language. Traditional Chinese language teaching cause the lack of high communicative competence. Therefore, the study preliminarily attempt to combine the theory of Communicative Language Teaching with Comprehensive Chinese teaching so as to search for a feasible and effective instruction which conforms to the teaching features of comprehensive Chinese course in Khon Kaen University. After Pre-test and Post-test and compared by SPSS (T-Test sig (2-tailed) = 0.00-0.05), the result show that in Listening skill the difference is significant (sig. (2-tailed) = 0.01), Speaking skill the different is significant (sig. (2-tailed) = 0.00), Writing skill the different is significant (sig. (2-tailed) = 0.03), only Reading skill which the difference is no significant(sig. (2-tailed) = 0.324). As a result after a semester using Communicative Language Teaching method in comprehensive Chinese course for Chinese major student in Khon Kaen University, CLT effectively improve student Chinese language achievement and help them to improve their Chinese listening, speaking and writing skill. Moreover, this teaching method is highly recognized by students. This verified the important and necessity of communicative language teaching method to improve Chinese major student Chinese communicative competence.